A Política Nacional de Assistência Estudantil (PNAES) e seu processo formativo - Guimarães, Gustavo Carrijo (2024)
Higher education in Brazil, historically marked by elitism and inequalities, faces the challenge of guaranteeing the right to education for all. The National Student Assistance Program (PNAES), created to promote the permanence of students in situations of social vulnerability in federal higher education institutions, emerged as an essencial public policy on facing dropout and retention and promoting the students' quality of life. It became necessary in light of other policies implemented by Lula and Dilma governments: REUNI, Quota Law, ENEM, and SISU. Along with the expansion and increased access, it is necessary to guarantee permanence for the adequate enjoyment of the right to education, which makes PNAES a crucial program for the consolidation of the democratic higher education model. However, PNAES faces institutional and budgetary fragilities, as well as instabilities in its legal positiveness. Therefore, it is fundamental to identify the qualitative character of its elaboration and to answer what type of public policy the program corresponds to in terms of State models. To this end, I conduct the research within the Marxist epistemology. For the technical means, I chose documentary and bibliographic research. I surveyed the history of Brazilian higher education and the central concepts of State and public policies. Following this, I analyzed the PNAES elaboration's main documents and made a comparative study between them, classified in terms of State models. My objective was to identify the PNAES' constitutive traits along its trajectory from its inception to its latest proposal. By analyzing the founding documents of the program, I was able to conclude that PNAES oscillates between the typical Welfare State models (social democratic, liberal, and corporatist) throughout its trajectory, under the influence of budgetary constraints to which it is subjected.